Does Pentraxin-3 contribute to the reduction of low-density lipoprotein levels by statin therapy? Pentraxin-3 and low-density lipoprotein after statin therapy - Vuković-Dejanović, Vesna; Spasojević-Kalimanovska, Vesna; Kalimanovska-Oštrić, Dimitra; Bogavac Stanojević, Nataša (Archives of Pharmacy, 2022)
Statins have been shown to decrease inflammatory markers, especially high sensitivity C reactive protein (hsCRP), in a dose-dependent manner. Pentraxin-3 (PTX3) is another important inflammatory biomarker from the pentraxin family that provides useful prognostic information and facilitates diagnostics of cardiovascular diseases. This study investigated the effect of statin therapy on PTX3 and hsCRP concentrations and whether statins acted synergistically with PTX3 and hsCRP concentrations in lowering LDL-C. The study group consisted of 90 patients undergoing coronary angiography. The results showed that statins reduced PTX3 concentrations (p=0.031). PTX3 and hsCRP levels were significantly different between subclinical and severe stenosis groups (p=0.011 and p=0.009, respectively). Statin therapy was significantly associated with lower PTX3 and LDL-C levels in multiple logistic analyses. The probability that statin therapy would achieve target LDL-C values was highest in patients with low PTX3 values (OR=3.683, p=0.040), while multiplicative interaction was 23.3. The effect of statins on PTX3 reduction was higher than on hsCRP. It can be suggested that statin therapy was more successful in patients with low PTX3 values.